Identification of Candidate Genes Associated With Hypoxia Tolerance in Trachinotus blochii Using Bulked Segregant Analysis and RNA-Seq - Liu, Yifan; Jiang, Tian; Chen, Youming; Gu, Yue; Song, Feibiao; Sun, Junlong; Luo, Jian (Frontiers in Genetics, 2021)
Golden Pompano (Trachinotus blochii) has rapidly developed into the one of the main valuable fish species in Chinese marine aquaculture. Due to its rapid growth, active metabolism, and high oxygen consumption, hypoxia will increase its mortality and cause serious economic losses. We constructed two experimental groups of fish with different degrees of tolerance to hypoxia, used BSR-Seq analysis based on genome and genetic linkage groups to locate SNPs and genes that were related to the differences in hypoxia tolerance. The results showed that hypoxia tolerance SNPs of golden pompano may be jointly determined by multiple linkage groups, especially linkage groups 18 and 22. There were 768 and 348 candidate genes located in the candidate regions of the brain and liver, respectively. These genes were mainly involved in anaerobic energy metabolism, stress response, immune response, waste discharge, and cell death. The prostaglandin-endoperoxide synthase 2 (PTGS2) on LG8, which is involved in the metabolism of arachidonic acid, has a G/A nonsynonymous mutation at position 20641628, and the encoded amino acid was changed from hydrophobic aspartic acid to asparaginate. The specific pathway of the RIG-I-like receptor signaling pathway in the liver may mediate the metabolic system and the immune system, linking glucose metabolism with immune regulation. The death of the hypoxia-intolerant group may be due to the accumulation of lactic acid caused by the activation of anaerobic glycolysis during the early stage of hypoxia stress, and the activation of type I interferon was inhibited, which resulted in decreased immunity. Among the genes involved in the RIG-I-like receptor signaling pathway, the CYLD Lysine 63 Deubiquitinase (CYLD) located on LG16 had a G/T nonsynonymous mutation at position 13629651, and the encoded amino acid was changed from alanine acid to valine. The interferon induced with helicase C domain 1 (Ifih1) located on LG18 has a G/C nonsynonymous mutation at position 16153700, and the encoded hydrophilic glycine was changed to hydrophobic alanine. Our findings suggest these SNPs may assist in the molecular breeding of hypoxia-tolerant golden pompano, and speculate that the balance of glucose and lipid metabolism plays a key role in Trachinotus blochii under acute hypoxia.